Paraplegia after Open Repair of Suprarenal Abdominal Aortic Aneurysm - Kim, Hyo Jun (Vasc Specialist Int, 2020)
Spinal cord ischemia after open repair of abdominal aortic aneurysm (AAA) is an unpredictable and devastating complication. We present a case report of a patient who developed paraplegia 6 hours after open repair of suprarenal AAA. A 74-year-old man presented with asymptomatic 5.5-cm suprarenal AAA, for which he underwent open repair under general anesthesia. The paraplegia was identified 6 hours after the operation. Postoperative magnetic resonance imaging showed T2 signal hyperintensity and swelling of the spinal cord, which were consistent findings with subacute spinal cord infarction. Although intravenous steroid was administered and lumbar cerebral spinal fluid drainage was instituted, his neurological outcome did not improve. He was discharged after vigorous rehabilitation but still has paraplegia and requires wheelchair for ambulation.